Phase-space characterization of negative ion beams for fusion - Carlo Poggi; Antonio Pimazzoni; Emanuele Sartori; Gianluigi Serianni (Nuclear Fusion)
Multi-grid, multi-aperture accelerators are used in ion sources of neutral beam injectors (NBIs) for fusion. Accelerators are typically optimized by numerical tools, usually taking the e-fold divergence as a valuable global indicator of the single beamlet optics. Nonetheless the velocity distribution of accelerated beamlets often deviates from ideal Gaussian profiles. Therefore an accurate characterization of the beamlets optics is essential, particularly for negative ion sources within the context of developing ITER NBIs, which pose challenging requirements on single beamlet optics. For this purpose, an Allison-type emittance scanner was installed in SPIDER, the prototype radio-frequency ion source of ITER heating neutral beams, and utilized to characterize the vertical phase-space of isolated beamlets. In this paper we present the characterization of the beamlets around perveance-match conditions using the Allison type emittance scanner, showing that the minimum divergence obtained is larger than the design value. The discrepancy is investigated using numerical simulations, which highlight the presence of a non-negligible temperature of the extracted negative ions, and of non Gaussian tails, which cannot be reproduced by a uniform thermal distribution of negative ions.